Review of carbonate hosted lead-zinc (copper) deposits and the geological factors affecting their shape, size and grade - McDonald, B (Rhodes University, Faculty of Science, Department of Geology, 1981)
From Introduction: For at least two centuries and a corresponding number of generations of geologists and miners there has been active argument concerning the origin of certain types of carbonate hosted mineral deposit. The characterization of the type itself was and still is debatable. Objections have been raised to grouping several examples under one heading because each has its individually distinctive features. Â·This is especially applicable to the carbonate hosted lead-zinc "sedimentary" deposits. The type that will be discussed in the text to follow is composed chiefly of galena, sphalerite, barite and fluorite, with pyrite , marcasite and chalcopyrite as conspicuous accessory ore minerals. Exceptions to this general copper deficient characteristic displayed by the sedimentary carbonate-hosted lead-zinc deposits are the deposits at Tsumeb and Kombat, Namibia. These deposits are hosted by the carbonate sequence of the Otavi Shelf sediments, and copper, in the form of tennantite, chalcopyrite and bornite, is the major ore constituent. Calcite, aragonite, dolomite and quartz are the commonest nonmetallic gangue minerals but siderite and silica may also be present. In contrast with other lead and zinc sulphide (volcanogenic) deposits, those to be considered here seldom carry noteworthy amounts of silver or any other precious metals. Commonly the country rock is a carbonate; limestone or dolomite, but deposits in. sandstone, shale and conglomerate are not unknown. Characteristic features are ore bodies that extend parallel or nearly so with the bedding although many such deposits are partly, or completely developed along crosscutting fissures and breccias. Some observers regard these fissure fillings as evidence for a magmatic source of the metals, whereas others regard them as an indication of remobilization of ions, metals or minerals orginally present in low-grade stratiform deposits elsewhere in the stratigraphic succession.
Keywords: Lead ores; Zinc ores; Copper ores; Sedimentology; Sedimentation and deposition